Fumigant and feeding deterrent activity of essential oils against Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae) - Silvi Ikawati; Toto Himawan; Abdul Latief Abadi; Hagus Tarno (Society for Indonesian Biodiversity, 2020)
Abstract. Ikawati S, Himawan T, Abadi AL, Tarno H. 2020. Fumigant and feeding deterrent activity of essential oils against Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae). Biodiversitas 21: 4301-4308. This study aimed to determine the fumigant and antifeedant activity of some plant essential oils against Cryptolestes ferrugineus. Essential oils were extracted from cinnamon (Cinnamomum verum), kaffir lime (Citrus hystrix), citronella grass (Cymbopogon nardus), zodea (Euodia suaveolens), and clove (Syzygium aromaticum). The extraction used the maceration method with n-Hexane as a solvent. The results of the experiments showed that all essential oils have fumigant toxicity. Fumigant toxicity of kaffir lime, citronella grass, zodea, and clove oil; eggs and pupae were more susceptible than adults and larvae, while for cinnamon, pupae and adults were more susceptible than eggs and larvae. Median Lethal Concentration (LC50) of all essential oils for eggs larvae, pupae, and adults respectively, for cinnamon were 17, 24, 9, and 12 ppm, for kaffir lime were 12, 17, 8 and 15 ppm, however, on citronella grass were 11, 22, 8, and 14 ppm, for zodea were 16, 22, 10 and 20 ppm, for clove were 11, 24, 7 and 14 ppm. The fifth essential oils showed antifeedant activity in a no-choice test against C. ferrugineus adults. Also, the fifth essential oils significantly reduced the relative growth rate (RGR), relative consumption rate (RCR), and food utilization (ECI) of C. ferrugineus adults. It shows that the essential oils have great potential as one of the storage pest control components.